CONTRIBUTION OF YEJELLA SHRI RAMULU CHAUDARI TO AYURVEDIC VETERINARY MEDICINE- A BIOGRAPHICAL RESEARCH STUDY - Prasad, *Goli Penchala; Swamy, R. K. (AYUSHDHARA, 2015)
Yejella Shri Ramulu Chaudari is a famous Ayurvedic Veterinarian of Andhra Pradesh. He had written many Veterinary books in an easily apprehensive way in local Telugu language. Yejella Shri Ramulu Chaudari had written many books on various aspects of cattle and horses including etiopathogenesis and treatment with Ayurvedic drugs from the year 1928. He ran Pashusamrakshana named journal, Ayurvedic veterinary college and hospitals, Sahadeva Ayurveda pharmacy for many years. In the field of Ayurvedic veterinary medicine he trained many graduates, farmers, servants and animal keepers of Jamindars, landlords, social workers and propagated Ayurvedic veterinary medicine. He got the authority in both Ayurvedic and Allopathic systems and tried to integrate both the systems. His publications are source for model integration studies of both Ayurvedic and modern systems of medicine. Further he strove hard for the propagation of Ayurvedic veterinary medicine through pamphlets, workshops, essays in local newspapers and local journals. He received many awards and got many testimonials and certificates for his good publications, for his thankfulness, valuable suggestions and dedication in the field of veterinary medicine. Many opulent landlords and Jamindars showed their genuine love and sincere support for his institution and publications. Many renowned allopathic physicians, public representatives, scientists in the field of veterinary medicine and Ayurvedic physicians appreciated his dedicated work and commitment in helping the poor through veterinary Ayurvedic medicine. He ran Ayurvedic Sahadeva Pashu vaidya pharmacy and developed many proprietary medicines like Janturakshini, Kshirojan, Asvabalavardhini, Krimihar, Garbhaka, Pashubalavardhini etc. and sold for reasonable prices. He was popular as Abhinava sahadeva for his contributions.